A calcium lactate treatment at harvest, growing system and refrigerated modified atmosphere can affect strawberry’s ´Camarosa´ postharvest quality? - Harris, Marcela Moira (2017)
Fil: Harris, Marcela Moira. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Vegetal. Cátedra de Horticultura. Buenos Aires, Argentina.